The Role of People's Oil Palm Plantations in the Economic Development of Aceh Tamiang Regency - Indriansyah, Muhammad; Safitri, Sri Ariani (Jurnal Indonesia Sosial Sains, 2025)
This study examines the role of smallholder palm oil plantations in the economic development of Aceh Tamiang Regency, Indonesia, a region pivotal to the nation’s palm oil history yet under-researched. Using a quantitative descriptive approach, the research analyzes secondary data (2019–2023) from the Central Statistics Agency and employs Location Quotient (LQ), Growth Ratio Model, and Klassen Typology to evaluate palm oil’s sectoral dominance, growth, and regional positioning. Findings reveal that palm oil is a leading commodity (LQ > 1), with production exceeding local demand and strong growth potential (positive Growth Ratio values). However, labor absorption remains low (LQ < 1), indicating a need for workforce-focused policies. The Klassen Typology classifies the sector as "advanced and rapidly growing," contributing significantly to regional GDP. The study’s novelty lies in its integrated analytical framework and focus on Aceh Tamiang’s unique challenges. Implications suggest enhancing labor opportunities through skill development, diversifying value chains (e.g., biofuel), and adopting sustainable certification (RSPO). This research provides actionable insights for policymakers to optimize palm oil’s economic benefits while addressing labor and sustainability gaps.